2017
DOI: 10.1007/s10561-017-9671-0
|View full text |Cite
|
Sign up to set email alerts
|

Donor cornea tissue in cases of drowning or water submersion: eye banks practice patterns and tissue outcomes

Abstract: Surgical use of donor corneal tissue from victims of water submersion (drowning or submersion secondary to death) remains controversial due to limited evidence about the quality of these tissues. To assess the safety of donor corneal tissue from victims of water submersion, an investigation of eye banks' practice patterns and tissue outcomes was conducted. All 79 Eye Bank Association of America accredited eye banks were contacted for a phone interview of practices regarding tissue from victims of water submers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Vijaykumar et al 7 conducted a retrospective multicenter review of a network of 79 eye banks. They categorized the eligibility for tissue procurement based on victims of water submersion (drowning or submersion secondary to death) and considered the type of water and duration of submersion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Vijaykumar et al 7 conducted a retrospective multicenter review of a network of 79 eye banks. They categorized the eligibility for tissue procurement based on victims of water submersion (drowning or submersion secondary to death) and considered the type of water and duration of submersion.…”
Section: Discussionmentioning
confidence: 99%
“…5 Despite being controversial, studies reported that corneal transplantation with tissues harvested from drowning victims has good outcomes. [7][8][9] Corneas harvested from drowning victims can contribute to the existing donor pool. The literature review highlights only a few studies on tissue characteristics, graft survival, and corneal outcomes in corneal tissues collected from drowning victims.…”
mentioning
confidence: 99%
See 1 more Smart Citation